A concepção de erro entre os professores de Matemática: Tensões entre falibilismo e absolutismo - Ramos, Syana Monteiro de Alencar (2015)
In the present study aimed to identify and analyze the error conceptions acquired throughout life for mathematics teachers of paradise. The concepts and visions built are established as truths at the heart of this professional as an individual and are reflected to the classroom for him as a teacher. Rationale for the study was carried out a literature review of literature addressing this issue or that relate to it. Among them we can mention the bank and liberating education and problem solving. The sources consulted point to a relationship between these axes. Both converge in order to seek improvements in teaching. Thus, there was the need to understand how the math teachers of paraíba realize the error having as parameter absolutism and fallibilism. It was also a comparison of these views with the resolution of issues and banking and liberating education. The investigation was made through a semi-structured questionnaire. The same was applied to 70 state teachers of paradise. The research is qualitative. Among the results there is the approximation of the absolutist features of most respondents.